1996
DOI: 10.21273/jashs.121.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Water Application Scheduling by Pan Evaporation for Drip-irrigated Tomato

Abstract: Tomatoes (Lycopersicon esculentum Mill.) were grown on an Arredondo fine sandy soil to evaluate the effects of water quantity applied by drip irrigation scheduled by pan evaporation in a 3-year study. Water was applied to polyethylene-mulched tomatoes at 0, 0.25, 0.50, 0.75, and 1.0 times pan evaporation in one application per day. Irrigation was also scheduled with tensiometers to apply water to maintain soil water tension above 10 cb. The response to irrigation varied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 3 publications
4
13
0
Order By: Relevance
“…During 2002, irrigation quantities were 34.4 cm with 10 kPa and 31.2l cm with 25 kPa and total marketable yield was unaffected by water treatment. In past work, maximum yields were produced with water quantities between 0.5 and 1.0 pan (Locascio and Smajstrla, 1996). In 2002, fruit yields were higher from plants that received CaSO 4 than from plants that received CaCl 2 or reduced K. This suggests the K rate was below the plants' requirements for optimal fruit production, and the reduction in K application in the higher irrigation 2002 season than in 2001 caused a reduction in marketable yield (Locascio et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…During 2002, irrigation quantities were 34.4 cm with 10 kPa and 31.2l cm with 25 kPa and total marketable yield was unaffected by water treatment. In past work, maximum yields were produced with water quantities between 0.5 and 1.0 pan (Locascio and Smajstrla, 1996). In 2002, fruit yields were higher from plants that received CaSO 4 than from plants that received CaCl 2 or reduced K. This suggests the K rate was below the plants' requirements for optimal fruit production, and the reduction in K application in the higher irrigation 2002 season than in 2001 caused a reduction in marketable yield (Locascio et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Less water is applied with tensiometer scheduling of water at 10 to 15 kPa on a coarse textured soil. Water use on tomato was 30 cm per crop with water scheduled to replace 0.75 pan and 17 cm used where irrigation was scheduled with magnetic switching tensiometers to apply water to maintain soil at 10 kPa (Locascio and Smajstrla, 1996;Smajstrla and Locascio, 1996). On fi ner textured soils, water is applied to maintain the soil at 20 to 50 kPa (Locascio et al, 1992).…”
Section: Microirrigationmentioning
confidence: 99%
“…in contrast, çetin et al (2002) found that tomato yield was highest at 100% pan evaporation replenishment (176 t ha -1 ). according to Locassio & Smajstrla (1996), total marketable tomato yields were highest at 1.0 pan (87t ha -1 ) and 0.75 pan (79.3t ha -1 ). The results obtained by these researchers were similar to our findings in terms of the highest marketable yields of tomato irrigated by drip for 100% pan evaporation replenishment.…”
Section: Irrigation Water Productivitymentioning
confidence: 97%